USE OF WILD EDIBLE PLANTS IN HUMAN NUTRITION DURING WAR IN BOSNIA AND HERZEGOVINA (W.BALKAN) - Redzic, S.; Redzic, A.; Biscevic, A. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
During war, especially in territories under siege, one of the biggest problems in survival of people is hunger [1]. Same was in surrounded Sarajevo, in Bosnia and Herzegovina, where inhabitants were kept in total blockage for over 1,400 days continuously. People lacked in all main ingredients, especially in flour, vegetables and fruits. First author of this study lived through all dreadful war occurrences and at the same time worked as an instructor in human survival by using edible wild plants. Parts of those experiences are provided in this study. Beside already achieved results, researches were continued during 1999-2004. By using method of ethno – botanical interview about 135 people of different sex and age were interviewed, in addition to field work, and determined were 124 species of wild plants. Out of 135 species, 240 parts were used (leafs, fruits, over ground parts) in making about 215 different preparations (salads, beverages, vegetable, spices, teas). Most plants had edibility rating 3, then 4 and 5 with distinguished nutritive and caloric values. Most important are the following: Taraxacum officinale, Plantago major, Urtica dioica, Malva sylvestris, Cichorium intybus, Arctium lappa, Tussilago farfara, Sedum telephium, Prunus spinosa, Cratagus monogyna and others. During winter, used were fruits of decorative species Chaenomeles japonica, Sempervivum tectorum and Sedum hispanica. As war progressed and hunger had more serious consequences, interest of all people became bigger for everything edible. This study proves that hunger is one of the strongest cohesion factors that unify different groups of people not only based on social, but on ethnical and ideological affiliations [2,3]. References: 1.Redzic, S.J. (2006). Ecology of Food and Nutrition, 45, 189-232. 2. Redzic, S.J. (2006). Ecology of Food and Nutrition, 45, 189-232. 3. Redzic, S. (1999). Pharmacia, 10, 28-41. Need to be returned to authors for further editing and revision.